2014
DOI: 10.1007/s13197-014-1293-y
|View full text |Cite
|
Sign up to set email alerts
|

Flaxseed—a potential functional food source

Abstract: There is currently much interest in phytochemicals as bioactive molecules of food. Functional foods are an emerging field in food science due to their increasing popularity among health conscious consumers. Flaxseed is cultivated in many parts of world for fiber, oil as well as for medicinal purposes and also as nutritional product. In this review, nutrients, anti-nutrients, functional properties, processing, metabolism and health benefits of bioactive molecules viz., essential fatty acids, lignans and dietary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
331
2
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 382 publications
(345 citation statements)
references
References 141 publications
4
331
2
8
Order By: Relevance
“…This was expected, since LNA is the precursor of EPA and DHA, while LA is the precursor of AA. 50 By the comparison of the results from TL (Figure 1) and the FA composition of the fish fillets (Table 3), it can be observed that for both treatments (TI (30) and TII (30) ) the TL increased significantly during the feeding time. However, the fish fillets from TII (30) incorporated significantly higher amounts of n-3 FAs, raising the nutritional lipid quality of the freshwater fish fed with the supplemented diet with JGSO.…”
Section: Fatty Acid Composition -Nile Tilapia Filletsmentioning
confidence: 92%
“…This was expected, since LNA is the precursor of EPA and DHA, while LA is the precursor of AA. 50 By the comparison of the results from TL (Figure 1) and the FA composition of the fish fillets (Table 3), it can be observed that for both treatments (TI (30) and TII (30) ) the TL increased significantly during the feeding time. However, the fish fillets from TII (30) incorporated significantly higher amounts of n-3 FAs, raising the nutritional lipid quality of the freshwater fish fed with the supplemented diet with JGSO.…”
Section: Fatty Acid Composition -Nile Tilapia Filletsmentioning
confidence: 92%
“…Flaxseed ( Linum usitatissimum L.) is a functional food that has attracted growing interest from researchers because it contains biologically active components such as dietary fibers, plant proteins, polyunsaturated fatty acids (PUFAs), and lignans, which play a beneficial role in the organism, enabling disease prevention (Rubilar and others ; Taylor and others ; Kajla and others ). Flaxseed oil (FO) contains approximately 57% alpha‐linolenic acid (ALA), being the richest ALA source.…”
Section: Introductionmentioning
confidence: 99%
“…Now a days, flaxseed has been recognized as potential functional food source owing to its bioactive components-omega-3 fatty acid, lignans and dietary fibre (Kajla et al, 2014). The seeds have a crisp, chewy texture and a pleasant, nutty taste.…”
Section: Introductionmentioning
confidence: 99%